2013
DOI: 10.1002/poc.3091
|View full text |Cite
|
Sign up to set email alerts
|

Combined 1 H NMR and DFT study of the solvent effects on the iron pentacarbonyl-catalyzed photo-assisted isomerization of allyl alcohol

Abstract: The relative rates of iron pentacarbonyl‐catalyzed photo‐induced isomerization of allyl alcohol to propanal in various solvents have been measured using 1H NMR spectroscopy. The reactions were run in linear and cyclic alkanes, alcohols, and amines in order to investigate solvent effects on the isomerization mechanism upon ultraviolet irradiation. The isomerization was efficient in nonane, hexane, cyclohexane, and benzene. The isomerization was very slow or completely suppressed in ethanol, propanol, isopropano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This first observation suggests that solvents with a high hydrogen‐bond accepting ability are inhibiting catalyst activity, possibly by a coordination with the metal centre of the aluminium catalyst, hence blocking the access of the aldehyde reactant to the active metal centre. This explanation has been reported in other homogeneous catalytic processes using similar type of catalysts . Solvation effects could also occur by producing solvation shells of solvent molecules around the reactant species, hence preventing the reactant from accessing such active sites .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This first observation suggests that solvents with a high hydrogen‐bond accepting ability are inhibiting catalyst activity, possibly by a coordination with the metal centre of the aluminium catalyst, hence blocking the access of the aldehyde reactant to the active metal centre. This explanation has been reported in other homogeneous catalytic processes using similar type of catalysts . Solvation effects could also occur by producing solvation shells of solvent molecules around the reactant species, hence preventing the reactant from accessing such active sites .…”
Section: Resultssupporting
confidence: 67%
“…Using such parameters it has been possible to elucidate solvent effects in a variety of homogeneously catalysed reactions. For example, Chase et al . studied the isomerization of allyl alcohol to propionaldehyde using an iron pentacarbonyl catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the polar hydroxyl group induces an electron density shift in IPC. Hydrocarbon solvents such as cyclohexane and other alkanes do not induce any deformation [21,22]. This specific solvent interaction may facilitate unique solvent-dependent reaction dynamics [21,40].…”
Section: Introductionmentioning
confidence: 98%
“…In solution, however, typically just one or two carbonyls are lost under comparable photoexcitation conditions [16][17][18][19][20]. It has been shown that in arene, alcohol and amine solvent media, 60-90% of iron pentacarbonyl (IPC) molecules may undergo structural and electronic deformations and weakly hexacoordinate with a single solvent molecule, forming an Fe(CO) 5 -solvent complex [21][22][23][24]. Similar studies have shown that Ru(CO) 5 interacts with a single solvent molecule via a nearly identical mechanism, albeit more strongly and to a greater extent than IPC [25,26].…”
Section: Introductionmentioning
confidence: 99%